IMPROVING THE QUALITY OF STUDENTS OF USHULUDDIN ISLAMIC BOARDING SCHOOL THROUGH ORGANIC VEGETABLE AGRICULTURE TRAINING - Isnaeni Hartanti; Dahlia; Zaenal Abidin (Khidmatan, 2023)
The Ushuluddin Islamic Boarding School is one of the Islamic boarding schools that is required to produce quality students not only in the religious field, but also in other fields such as agriculture. Santri can not only recite the Koran, but must also have skills as provisions to live in society. The problem faced by some students is the lack of interest in agricultural activities, students still do not understand the many benefits of vegetables for health. There are many reasons behind this, including the lack of teachers/administrators who care about the importance of eating vegetables and a lack of skills in farming. The purpose of this service is to observe and accompany and find out the methods used by the students in developing organic vegetables in the boarding school environment. Because the object of service this time is a religious education institution, the process of learning practice through direct agricultural activities is carried out every Saturday and Sunday according to the pesantren agenda. The approach used in this service is PAR (Participation Action Research). The method used in this service is training. Practically the dedication can help develop organic vegetable cultivation at the Ushuluddin Islamic Boarding School.